Becoming An Existential Therapist (Existential Analysis: Journal of the Society for Existential Analysis, 2014)
Original version of an essay written for the programme 'Existential Me', The Essay – BBC Radio 3 – short version read for BBC 3 on 15 November 2013 and published in the Hermeneutic Circular.